AESTHETIC VALUES IN A COLLECTION OF CHILDREN'S POEMS BY MAHAYA MOHD. YASSIN - Nik Muhamad Affendi, Nik Rafidah; Abdul Fatah, Muhammad Faiz Fadhli; Che Rodi, Rozita (Universitas Islam Malang, 2025)
Abstract: Children's literature provides children with a personal experience through its dual function as a medium of education and entertainment. Works categorized as children's literature also embody aesthetic values that are important for the development of the mind and emotions. One such form is poetry, a beautiful Malay art form that has existed since ancient times. Poetry is not only intended for adults but has also attracted children to read and appreciate it. The problem addressed in this study stems from the gap in previous research, which has given little attention to the aesthetic values in children's poetry. Therefore, this study was conducted to identify and analyze the aesthetic values in Kumpulan Puisi Kanak-kanak: Buku by Mahaya Mohd. Yassin. The study employed library research and textual analysis, guided by the Teori Puitika Sastera Melayu proposed by Muhammad Haji Salleh. The findings reveal five aspects of aesthetic values embedded in the work, namely aesthetics from the perspective of emotions, nature, language, human creation, and wisdom. These five aspects successfully demonstrate the richness of aesthetic values in Kumpulan Puisi Kanak-kanak: Buku by Mahaya Mohd. Yassin. Hence, it is hoped that this study will provide meaningful contributions to future research on children’s literature, particularly in discussions related to aesthetics.